Pakistan - Reforming Provincial Finances in the Context of Devolution : An Eight Point Agenda - World Bank (Washington, DC, 2013)
Public finances in Pakistan have been characterized by unsustainably, high fiscal deficits; poor revenue mobilization; a persistent trend of centralization; massive vertical imbalances between the federal, and provincial governments; problematic expenditure structures; weak financial management; the atrophy of local governments; and, lack of accountability. Recently the Government has announced a bold, and potentially path-breaking devolution initiative to address some of these problems, by establishing strong, accountable local governments. Focussing on the provinces, their financial health, and the delivery of infrastructure, and public services, this report puts forward recommendations for reform in the following areas: 1) adjusting federal-provincial fiscal relations to reduce vertical fiscal imbalances; 2) improving the effectiveness of public services through devolution; 3) prioritizing provincial expenditures in favor of critical non-wage operations and maintenance, and reducing the dominant share of establishment costs; 4) improving expenditure programming, and management; 5) restructuring provincial civil services; 6) mobilizing provincial revenue, streamlining tax structures, and rationalizing user charges; 7) strengthening financial management; and, 8) developing systematic approaches to provincial debt management.